Laboratory investigation of the influence of aluminum hydroxide on the compressive strength of nickel slag-stabilized soft soils - Ichsan Rauf; M. Taufiq Yuda Saputra; Heryanto Heryanto; M. Fatahilla Marsaoly (AIMS Materials Science)
Chemical stabilization is considered a more effective and efficient method for improving soft soil in road foundation construction. Nickel slag, a byproduct of the nickel industry, has the potential to be developed as an environmentally friendly pozzolanic material for soft soil improvement. Our previous research has shown that nickel slag enhances the mechanical properties of high-plasticity organic soil but fails to meet road foundation standards. As such, additional materials are needed to achieve the required specifications. This study aims to analyze the effect of adding aluminum hydroxide [Al(OH)3] to soil stabilized with nickel slag. The addition of Al(OH)3 is based on weight ratios of nickel slag at 1.5, 2.5, and 3.5. The effectiveness of adding nickel slag was assessed based on the unconfined compressive strength (qu) of the mixture matrix. In addition, mineral characterization of the mixture matrix was tested using X-ray diffraction (XRD) to observe changes in mineral fractions. The results of this study indicate that the addition of Al(OH)3 can improve the mechanical performance of soft clay soil better than soil stabilized with nickel slag alone, with the 1.5% weight ratio providing the highest compressive strength value of 237.39 kPa. This improvement may be due to the formation of pozzolanic reactions, including C–S–H, C–A–H, and C–S–A–H, as shown by the XRD test results.